Leveraging Evolving Artificial Intelligence Solutions and Collaborative Team Dynamics to Drive Organizational Transformation - Erwin, Erwin; Hadi, Achmad Setyo (Institut Bisnis dan Informatika Kesatuan, 2026)
Digital transformation driven by advances in artificial intelligence technology has become a strategic priority for organizations in various global industrial sectors. However, in Indonesia, AI implementation often faces obstacles stemming from limited collaborative capabilities, organizational cultural resistance, and low readiness of human resources to adapt to technological changes. This study aims to empirically examine the mediating role of team collaboration in the relationship between the adoption of AI technology and the success of organizational transformation. The research approach uses a quantitative method based on SEM-PLS with data collected from 400 respondents in various industrial sectors that have implemented AI. The results show that AI adoption has a positive and significant effect on organizational transformation through improved operational efficiency, decision-making quality, and business innovation. In addition, AI adoption also increases the effectiveness of team collaboration in cross-functional coordination and communication. The mediation analysis confirms that team collaboration is an important link between AI adoption and successful organizational transformation. In conclusion, the synergy between technological capabilities and human dynamics is the main key for organizations in achieving adaptive and sustainable digital transformation.